KENAKALAN REMAJA DAN PENGANGGURAN - B, Mahirah (Universitas Islam Negeri Alauddin Makassar, 2017)
To anticipate the increasing number of unemployed people who are not or have not yet found employment, it is necessary to provide early education for entrepreneurs and provision of skills to the students so that if they are unable to continue their studies or have not found employment, they can solve it by pioneering Employment in the field of skills accompanied by entrepreneurial mental attitude, courageous, mighty, tenacious, diligent, active, creative, high moral (religious), sensitive to the meaning of the environment, independent, to create employment and not just job seekers, Reduce unemployment and alleviate poverty / misery of community members